Simulating the Bargaining Model of War. Issue 4 (19th October 2015) - Haynes, Kyle
ABSTRACT: This article outlines a classroom simulation for teaching the bargaining model of war. This model has become one of the most important theories of international conflict, but the technical notation often used to illustrate it is troublesome for some students. I describe a simple card game that can be integrated into a broader strategy for conveying the bargaining model's core insights. I also highlight ways in which the game can be modified to focus on different aspects of the model's logic.